2009
DOI: 10.1186/1477-7827-7-140
|View full text |Cite
|
Sign up to set email alerts
|

Human male gamete endocrinology: 1alpha, 25-dihydroxyvitamin D3 (1,25(OH)2D3) regulates different aspects of human sperm biology and metabolism

Abstract: BackgroundA wider biological role of 1alpha,25-Dihydroxyvitamin D3 (1,25(OH)2D3), the active metabolite of vitamin D3, in tissues not primarily related to mineral metabolism was suggested. Recently, we evidenced the ultrastructural localization the 1,25(OH)2D3 receptor in the human sperm. However, the 1,25(OH)2D3 action in human male reproduction has not yet been clarified.Methods and ResultsBy RT-PCR, Western blot and Immunofluorescence techniques, we demonstrated that human sperm expresses the 1,25(OH)2D3 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 55 publications
4
101
1
3
Order By: Relevance
“…The vitamin D receptor is expressed in human sperm cells, and 1,25-dihydroxyvitamin D concentration may affect sperm survival and the acquisition of fertilizing ability of sperm cells. 3,4 Vitamin D status is assessed by measuring P-25OHD concentration 5 and is considered to be replete at P-25OHD concentrations 450 nmol/l, although recent studies have suggested that only P-25OHD 480 nmol/l should be considered as an optimal vitamin D status for non-skeletal outcomes. 6 P-25OHD insufficiency is widespread in all age groups, including younger women with childbearing potential.…”
Section: Introductionmentioning
confidence: 99%
“…The vitamin D receptor is expressed in human sperm cells, and 1,25-dihydroxyvitamin D concentration may affect sperm survival and the acquisition of fertilizing ability of sperm cells. 3,4 Vitamin D status is assessed by measuring P-25OHD concentration 5 and is considered to be replete at P-25OHD concentrations 450 nmol/l, although recent studies have suggested that only P-25OHD 480 nmol/l should be considered as an optimal vitamin D status for non-skeletal outcomes. 6 P-25OHD insufficiency is widespread in all age groups, including younger women with childbearing potential.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of glucose on the fertilizing ability of sperm appears to be mediated by the pentose phosphate pathway (PPP) (Miraglia et al, 2010), and G6PDH is the key rate-limiting enzyme in this metabolic pathway, and has been shown to be functional in human spermatozoa (Aquila et al, 2009). As shown in Fig.7A, PGJ2 activates G6PDH activity at concentrations of 10 and 20mmoll -1…”
Section: Pparγ Affects G6pdh Activity and Acrosome Reaction In Pig Spmentioning
confidence: 91%
“…The conversion of NADP + to NADPH, catalyzed by G6PDH, was measured by the increase of absorbance at 340nm, as previously described (Aquila et al, 2005b;Aquila et al, 2006;Aquila et al, 2009).…”
Section: G6pdh Activity Assaymentioning
confidence: 99%
See 2 more Smart Citations